Parent Involvement in School Programs: How Parents are Actively Involved in Islamic Kindergarten - Amalia, Nur Fatihah; Maryatun, Ika Budi (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
The purpose of this study is to describe parental involvement in school programs at Nurul Iman Islamic Kindergarten, Mataram City, as an effort to support the advancement of early childhood education (ECE). This research employed a qualitative approach using a case study method. Data collection techniques were carried out through triangulation, and data analysis was conducted inductively/qualitatively, with the researcher serving as the primary instrument. The study subjects included classroom teachers, the kindergarten principal, and parents of the children. Data analysis was conducted systematically by organizing, categorizing, synthesizing, and interpreting data from interviews, field notes, and documentation. The results indicate eight forms of parental involvement in school programs, including Committee Meetings, Inspiration Classes, Parent Classes, Parenting Classes, Sabtu Budaya, Outing Classes, Parent-Child Competitions, and the Maulid Nabi celebration. This involvement significantly benefits and supports the educational development of children. The parental involvement programs were successfully implemented and aligned with the planned objectives. Parents were not merely financial supporters but also participants, supporters, decision-makers, program implementers, and school committee members. This demonstrates strong collaboration between the school and parents in supporting early childhood education. The study, conducted in a single Islamic kindergarten, limits generalizability to broader contexts. Future research should compare diverse educational settings, incorporate parent surveys, and focus on long-term impacts. Reliance on interviews and documentation may overlook socio-economic influences. Additionally, researcher subjectivity suggests the need for more standardized methodologies.